The neolithic settlement of Knossos in Crete : new evidence for the early occupation of Crete and the Aegean islands - Efstratiou, Nicholas; Karetsou, Alexandra; Ntinou, Maria (Prehistory monographs, 2013)
The site of Knossos on the Kephala hill in central Crete is of great archaeological and historical importance for both Greece and Europe. Dating to 7000 B.C., it is the home of one of the earliest farming societies in southeastern Europe, and, in the later Bronze Age periods, it developed into a remarkable center of economic and social organization within the island, enjoying extensive relations with the Aegean, the Greek mainland, the Near East, and Egypt. After the systematic excavation of the deep Neolithic occupation levels by J.D. Evans in the late 1950s and later and more limited investigations of the Prepalatial deposits undertaken primarily during restoration work, no thorough exploration of the earliest occupation of the mound had been attempted. This monograph fills the gap, detailing the recent studies of the stratigraphy, architecture, ceramics, sedimentology, economy, and ecology that were a result of the opening of a new excavation trench in 1997. Together, these studies by 13 different contributors to the volume re-evaluate the importance of Neolithic Knossos and place it within the wider geographic context of the early island prehistory of the eastern Mediterranean.